2011
DOI: 10.1016/j.strusafe.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling same-direction two-lane traffic for bridge loading

Abstract: Publication informationStructural Safety, 33 (4-5): 296-304Publisher Elsevier This is a form of smoothed bootstrap in which kernel functions are used to add randomness to measured traffic scenarios. It is shown that it gives a better fit to the measured data than models which assume no correlation. Results are presented from long-run simulations of traffic using the different models and these show that correlation may account for an increase of up to 8% in lifetime maximum loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…In addition, various other sources provide recommendations for WIM data filtering and validation (FHWA 2001;Pelphrey and Higgins 2006;Tabatabai et al 2009;O'Brien and Enright 2011). Other efforts include those of Raz et al (2004), who proposed a data mining approach for automatically detecting anomalies in WIM data, and Monsere et al (2008), who studied methods for collecting, sorting, filtering, and archiving WIM data to facilitate development of high-quality long-term records.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various other sources provide recommendations for WIM data filtering and validation (FHWA 2001;Pelphrey and Higgins 2006;Tabatabai et al 2009;O'Brien and Enright 2011). Other efforts include those of Raz et al (2004), who proposed a data mining approach for automatically detecting anomalies in WIM data, and Monsere et al (2008), who studied methods for collecting, sorting, filtering, and archiving WIM data to facilitate development of high-quality long-term records.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that the assumptions on weight correlation are entirely based on judgment, as almost no data are available (Kulicki et al 2007). OBrien and Enright (2011) show that correlated traffic gives a better fit to the measured data than models which assume no correlation. Their results lead to the conclusion that correlation may account for up to an 8% increase in lifetime maximum loading.…”
Section: Introductionmentioning
confidence: 93%
“…For example, it is found that there is a significant peak in average GVW in the fast lane when the inter-lane gap is around zero (OBrien and Enright 2011). By definition, gaps become smaller as traffic flow rates increase, but WIM measurements also exhibit some dependence between gaps and GVW (Enright and OBrien 2012).…”
Section: Load Modellingmentioning
confidence: 99%
See 2 more Smart Citations